2000
DOI: 10.1177/00220345000790020201
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-mediated Gene Transfer to Mouse Salivary Glands

Abstract: Adenoviral vectors effectively transfer genes to rat salivary glands. However, potent immune responses limit their use in vivo. Mice offer more opportunities than rats for the study of these immune processes. We first established conditions for infection of mouse salivary glands, with an adenoviral vector. The effects of time, viral dose, viral diluent buffer volume, and dexamethasone on expression of a transgene, luciferase, were determined by means of the recombinant vector AdCMVluc. Optimal luciferase expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 28 publications
5
41
0
Order By: Relevance
“…The only clinical trial to date involving gene transfer Ultrasound-assisted gene transfer to the salivary glands MJ Passineau et al to the salivary glands has used an Ad vector, which Baum and colleagues have shown to elicit substantial inflammation in the gland, 23,29 presumably leading to functional impairment (which has been proposed to be mainly reversible 30 ). Our findings are in general agreement with earlier work in this field, indicating that transient physical disruption of cell membranes by local ultrasound-induced cavitation is not permanently injurious to the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…The only clinical trial to date involving gene transfer Ultrasound-assisted gene transfer to the salivary glands MJ Passineau et al to the salivary glands has used an Ad vector, which Baum and colleagues have shown to elicit substantial inflammation in the gland, 23,29 presumably leading to functional impairment (which has been proposed to be mainly reversible 30 ). Our findings are in general agreement with earlier work in this field, indicating that transient physical disruption of cell membranes by local ultrasound-induced cavitation is not permanently injurious to the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…8,22,41 Briefly, male mice (7 weeks old) were anesthetized with ketamine (60 mg/ml, 1 ml/g body weight; Phoenix Scientific, St Joseph, MO, USA) and xylazine (8 mg/ml; Phoenix Scientific), by i.m. injection, then administered atropine (0.5 mg/kg body weight, i.m.…”
Section: Raav Vector Administration Into Mouse Salivary Glandsmentioning
confidence: 99%
“…Notably, for viral-mediated gene therapy in humans, the SGs offer several advantages with respect to other organs: i) the encapsulation of the SG tissue prevents the dissemination of the virus in the rest of the body (Baum et al, 2004;Voutetakis et al, 2004), ii) in case of potential health issues the SGs can be removed since they are not essential for life, iii) the differentiation of the cells provides a relatively stable cell populations for non-integrating vectors, and iv) duacrine (both exocrine and endocrine) protein secretion allows to direct the expressed molecules into either the saliva or the blood stream (Baum et al, 2004). Numerous studies have shown successful gene transfer into both rat and mouse submandibular glands using viral-based approaches, which offer the advantage of a more robust expression of the transgenes (Andresen et al, 2009;Baum and Tran, 2006;Delporte et al, 1996;Honigman et al, 2001;Mastrangeli et al, 1994;Morita et al, 2011;Palaniyandi et al, 2011;Perez et al, 2011;Samuni et al, 2008;Wang et al, 2000;Zheng et al, 2009). However, non viral-mediated approaches have also been utilized, although limited to a small percentage of the cells in the parenchyma (Goldfine et al, 1997;Honigman et al, 2001;Niedzinski et al, 2003a;Niedzinski et al, 2003b;Passineau et al, 2010;Sramkova et al, 2009).…”
Section: Delivery Of Molecules Drugs and Gene Transduction In The Samentioning
confidence: 99%